Introduction - ICW, Likhaan (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
WHEN THE UNIVERSITY of the Philippines Institute of Creative Writing (UPICW) first conceived of the Likhaan Journal many years ago, we envisaged an annual selection of the best new writing in Filipino and English with which we could introduce contemporary Philippine literature to our people and the rest of the world.